Other people's money : the corporate mugging of America - Prins, Nomi (New York New press, 2004)
"Critical, independent voices are seldom found within the citadels of international finance. That’s what makes Nomi Prins unique. During fifteen years as an executive at skyscraping banks like Goldman Sachs, Bear Stearns, and Lehman Brothers, Prins never lost her ability to see the broader picture. She walked away from the game in 2002 out of disgust with the burgeoning corporate corruption, just as its magnitude was becoming clear to the public. In this acclaimed exposé, named one of the best books of 2004 by The Economist, Barron’s, Library Journal, and The Progressive, Prins provides fascinating firsthand details of day-to-day life in the financial leviathans, with all its rich absurdities. She demonstrates how the much-publicized fraud of recent years resulted from deregulation that trashed the rules of responsible corporate behavior, and not simply the unbridled greed of a select few. While the stock market roared on the back of phony balance sheets, executives made out like bandits and Congress looked the other way. Worse yet, as the new foreword to this edition makes clear, everything remains in place for a repeat performance" (from publisher's page)
Prologue : midsummer night's dream -- Introduction -- 1. The bank wars -- 2. Scratching backs : banks and corporations -- 3. Deregulation and creating instability -- 4. Enron, energy, and entropy -- 5. Telecom implosion -- 6. Examination and reform? --
Includes bibliographical references (P: 299-324)
Keywords: Economic conditions; ECONOMIC CONDITIONS; CORPORATE CORRUPTION; CORPORATIONS; SMUGGLING; INVESTMENT BANKING; USA